Edukasi Prosedur Pengambilan, Penanganan Dan Pengiriman Spesimen Nasofaring Dan Orofaring Pada Pasien Covid-19 Kepada Petugas Puskesmas Remaja - Kamil, Kamil; Raudah, Siti (Program Studi Teknologi Laboratorium Medis, ITKES Wiyata Husada Samarinda, 2022)
Coronavirus 2019 (Covid-19) is an infectious disease caused by acute respiratory syndrome coronavirus 2 (Sars-CoV-2). This disease was first discovered in December 2019 in Wuhan, the capital of China's Hubei Province, and has since spread globally worldwide, resulting in the 2019-2020 coronavirus pandemic. This virus is spread by coughing or sneezing (droplets) that come out of the mouth or nose hit someone or fall on the surface of nearby objects, and then are touched by other people. Covid-19 can cause pneumonia, acute respiratory syndrome, kidney failure, and even death in severe cases. Purpose: to increase knowledge regarding procedures for taking, handling and sending nasopharyngeal and oropharyngeal specimens in Covid-19 patients. Method: this activity is by conducting training on techniques for taking, handling and sending oropharyngeal and nasopharyngeal specimens in Covid-19 patients. Results: health workers have knowledge about the symptoms of Covid-19, ways of prevention, and procedures for taking, handling and sending nasopharyngeal and oropharyngeal specimens in Covid-19 patients. Conclusion: the importance of health workers' knowledge regarding the collection, handling and delivery of nasopharyngeal and oropharyngeal specimens in Covid-19 patients.